Validation of PIM 3, Prism III, and Pelod 2 Scores As Predictors of Mortality in Acute Respiratory Distress Syndrome in Pediatric Intensive Care Unit - Sihombing, Rina Margareth; Suparyatha, Ida Bagus Gede; Putra, I Gusti Ngurah Sanjaya (Eduvest - Journal of Universal Studies, 2025)
Acute Respiratory Distress Syndrome (ARDS) is a life-threatening condition in pediatric patients characterized by alveolar fluid accumulation that disrupts gas exchange. Various scoring systems—Pediatric Index of Mortality 3 (PIM 3), Pediatric Risk of Mortality III (PRISM III), and Pediatric Logistic Organ Dysfunction 2 (PELOD 2)—are utilized to estimate mortality, disease severity, and organ dysfunction. However, their validation specifically in pediatric ARDS remains limited. This prospective cohort study aims to evaluate the predictive validity of PIM 3, PRISM III, and PELOD 2 in children aged 1 month to 18 years diagnosed with ARDS and admitted to the Pediatric Intensive Care Unit (PICU). A total of 60 patients were enrolled, with 16 observed for a full 28-day period and 44 reaching clinical outcomes earlier (19 deaths, 25 survivals). Each scoring system was assessed using Receiver Operating Characteristic (ROC) analysis to determine optimal cut-off values for mortality prediction. The PIM 3 score with a cut-off of ≥6.8 yielded a sensitivity of 90.0% and specificity of 95.0%. PRISM III with a cut-off of ≥26 showed 85.0% sensitivity and 100% specificity, while PELOD 2 with a cut-off of ≥9 demonstrated similar performance (85.0% sensitivity, 100% specificity). Among the three, PIM 3 exhibited superior sensitivity for mortality prediction. These findings support the clinical utility of PIM 3 as a more responsive tool for early risk stratification in pediatric ARDS, aiding in timely and targeted interventions.